Venezuelan migrant families: experiences of educational inclusion from a labor and cultural perspective - Panizo Toapanta, Alex (2024)
Venezuela’s population movement is the largest in Latin America, currently seven million Venezuelans have left their country. According to statistics from the Interagency Coordination for Refugees and Migrants of Venezuela (2023): more than six million people have moved to Latin America and the Caribbean. The objective of this research is to know the process of educational inclusion of Venezuelan boys, girls and adolescents in the public educational system. It is hypothesized that education depends on two factors: the employment situation of the parents and their immigration status. Results show that learning is linked to a cultural, symbolic and social dynamic. Furthermore, Ecuador lacks a public policy for the inclusion of migrants in daily life and the recognition of their rights. On the other hand, the training of teachers with an intercultural approach and a global vision is urgent and transcendental.